STUDENTS’ VOCABULARY MASTERY THROUGH ENGLISH SONGS AT MADRASAH ALIYAH NEGERI 1 HALMAHERA UTARA - Saiful Latif; Mardia A Rahman (Jurnal Bilingual, 2020)
The aim of this research is to know the extent to which the use of English song improves students’ vocabulary at Madrasah Aliyah Negeri 1 Halmahera Utara. This research was quantitative research by using pre-experimental design with one group pretest-posttest. The sample of this research was 20 students in class  X-3 Social science students by using convenience sampling technique. The instrument used in the research was the song lyrics. The students’ answer the question by determining noun, verb and adjective of  vocabulary consisting of 50 items. The data were analyzed by using t-test. It was found that teaching vocabulary by using English Song helped the students to master vocabulary. Based on the data analysis, teaching by using English Song could significantly improve students’ vocabulary.The research  shows the score of pre-test and posttest as follow:  pretest 58.9 score and posttest 75.1 score, and T-count value obtain 12.7 and t critic 1.729 at the significant level 0.05. It means t-count is higher that t-critic. The null hypothesis (H0) stating that teaching vocabulary through English song cannot improve students vocabulary is rejected and the alternative hypothesis (Hi) stated that teaching vocabulary through English song can improve students’ vocabulary mastery at Madrasah Aliyah Negeri 1 Halmahera Utara is accepted.